INCONTRO TRA I SISTEMI INFORMATIVI GEOGRAFICI E LA GEOPOLITICA: IL CASO DELLA CRIMEA - Foria, Federico; Cavaliere, Mariassunta (GEOmedia, 2014)
The relationship between the Geographic Information Systems (GIS) and the geopolitics through the case study of the recent events in Crimea. The possibility of the scientific-humanistic pair and the usage of GIS technology at the service of the geopolitics. The analysis of the territory and his components, explaining the reasons of the most recent events and making future predictions.